INTERNAL AUDIT IN DEVELOPED COUNTRIES AND THE POSSIBILITIES OF ITS APPLICATION IN THE ECONOMY - Khaydarov, Bakhrom (Science technology&Digital finance, 2023)
In the article, the internal audit of developed countries and its application in the economy, the organization of internal audit, the development of the methodology of performance evaluation in accordance with international standards, and internal and external audit are not opposite to each other. On the contrary, there are reasons why they complement each other